Ultra-wideband tunable transparent all-dielectric absorber based on a saline water-filled PMMA periodic structure - Zeyu Pan; Haibin Wu; Ye Tian; Bo Lv (AIP Advances)
With the rapid development of electromagnetic technology, the demand for high-performance microwave absorbing materials is increasing. This paper proposes a novel design for an ultra-wideband, transparent, and tunable all-dielectric absorber based on a saline water-filled polymethyl methacrylate periodic structure. The performance of the absorber is comprehensively evaluated through theoretical analysis, numerical simulations, and effective medium theory. The results demonstrate that the designed absorber achieves an absorption rate of over 90% in the frequency range of 23.75–47.01 GHz, showcasing excellent wideband characteristics. The absorber also exhibits good angular stability, maintaining high absorption efficiency even at a large incidence angle of 60°. By adjusting the temperature and concentration of the saline water, dynamic tuning of the absorption band can be achieved, providing flexibility for different application scenarios. Analysis of the electric field distribution and power loss density reveals the absorption mechanism, confirming the critical role of saline water in the absorption process. The effective medium theory further explains the wideband characteristics and excellent impedance matching of the absorber. This study not only presents a novel absorber design but also provides important theoretical and practical guidance for the development of high-performance, environmentally friendly, and tunable microwave absorbing materials, with potential applications in addressing electromagnetic environmental pollution and electromagnetic compatibility issues.